a new species of Tapinocyba (Araneae, Linyphiidae) with a redescription of Tapinocyba minuta (Emerton) - Dupérré, Nadine; Paquin, Pierre (Zootaxa, 2005)
The identity of Tapinocyba minuta is clarified by examination of the type-series and the species is redescribed and illustrated. Tapinocyba prima new species, a distinct species previously confused with T. minuta, is also described and illustrated. Collection data, habitat and distribution are given for the two species. Tapinocyba prima new species has a widespread northern distribution with possible disjunct populations found at high elevations on the East Coast, while T. minuta has a more restricted distribution along a trans-continental boreal corridor.